Analisis Sistem Resi Gudang Sebagai Alternatif Pembiayaan Petani Ketika Deflasi - Hasanah, Nisa Maulida; Pratama, Muhammad Ath-Thaariq (Legal Standing : Jurnal Ilmu Hukum, 2025)
The Central Statistics Agency released its latest report on economic conditions in Indonesia, which has experienced deflation for 5 consecutive months. During this time, people's purchasing power continued to decline, making it difficult for farmers and fishermen to sell their produce at reasonable prices. The declining purchasing power makes many farmers or fishermen throw away their products because they cannot be stored. The government has created a Warehouse Receipt System (SRG) that aims to allow farmers, fishermen and others to store their commodities in a standardized warehouse. In addition, the SRG also includes a guarantee mechanism that allows for financing. Farmers and fishermen can store their products in SRG warehouses for a long time, but still get money for production capital with financing that makes Warehouse Receipts as collateral objects. SRG can be a solution for farmers and fishermen in the face of deflation or a decline in purchasing power with production continuing even though sales are slower than usual.